A novel extracellular nucleotide receptor coupled to phosphoinositidase-C in pituitary cells. - Davidson, J; Wakefield, I; Sohnius, U; Van Der Merwe, P; Millar, R (1990)
In primary cultures of sheep pituitary cells extracellular nucleotides stimulated rapid increases in inositol tris- and bisphosphate, accompanied by intracellular Ca2+ mobilization. A similar stimulation of inositol phosphate production by extracellular nucleotides was observed in rat and baboon pituitary cells. The inositol phosphate response to nucleotides was greater than that elicited by any of the known hypothalamic releasing peptides. UTP, ATP, and ATP gamma S were the most potent agonists, with EC50 values for inositol phosphate production of 1.2, 2.6, and 2.7 microM. The relative potencies of a range of nucleotides indicates that the pharmacological specificity of the pituitary nucleotide receptor is different from that of the previously characterized P2X and P2Y purinoceptors present in other tissues. Increasing extracellular Mg2+ concentrations caused a shift to the right of the ATP dose-response curves, indicating that the predominantly active agonist species is not MgATP and may be ATP4-. In the absence of both Ca2+ and Mg2+ (1 mM EDTA) ATP stimulated inositol phosphate production with high potency (EC50 = 200 nM), indicating that an ectokinase or ecto-ATPase reaction is not involved in its mode of action. Phosphoinositidase-C activation by ATP was insensitive to pertussis toxin. The magnitude of the inositol phosphate and 45Ca2+ responses to extracellular nucleotides indicates that a substantial fraction of the cells in primary pituitary cultures bears nucleotide receptors. None of the major pituitary hormones appear to be released by extracellular nucleotides. The cell types in the pituitary that bear these nucleotide receptors are at present unidentified.